2009
DOI: 10.1590/s1516-635x2009000200007
|View full text |Cite
|
Sign up to set email alerts
|

Fowlpox: identification and adoption of prophylactic measures in backyard chickens in Bahia, Brazil

Abstract: This paper describes the identification of an outbreak of fowlpox in backyard chickens in two villages the state of Bahia, the intervention strategy to control the disease by adopting health measures and vaccination, as well as the impact of the intervention. The diagnosis was based in clinical and laboratory data. After the diagnosis was confirmed, control measures and the vaccination of non-infected birds were recommended. Finally, the impact of the intervention on reincidence of the disease was evaluated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 7 publications
4
18
0
1
Order By: Relevance
“…Usually the fowlpox is a self-limiting disease and has milder manifestations, as reported by Silva et al (2009) in Brazilian free-range chickens. In the present case, a challenger viral strain might have disseminated to turkey flocks of the Triângulo Mineiro region.…”
Section: Discussionmentioning
confidence: 90%
“…Usually the fowlpox is a self-limiting disease and has milder manifestations, as reported by Silva et al (2009) in Brazilian free-range chickens. In the present case, a challenger viral strain might have disseminated to turkey flocks of the Triângulo Mineiro region.…”
Section: Discussionmentioning
confidence: 90%
“…Fallavena et al (2002) reports the presence of FWPV in Dermal Squamous Cell Carcinoma (DSCC) also in broiler chickens using a nested PCR. Silva et al (2009) reports the presence of Fowlpox in backyard chickens by clinical signs and confirming the diagnosis by histopathology. Vargas et al (2011) reported an infection by Avian poxvirus in barn owl, and Pereira et al (2014) reported a cutaneous tumor-like lesions associated with infection by APV in a Dendrocygna autumnalis.…”
Section: Discussionmentioning
confidence: 76%
“…It's used to differentiate FPV from other APVs because it's highly conserved. FPV140 is highly antigenic and immunodominent [1][2][3][4]6,[8][9][10][11][12][13][14][15]17,18].…”
Section: Fpv Related To Genus Avipox (Apvs) Apvs Belong To Subfamilymentioning
confidence: 99%